Preschool teachers' knowledge and attitudes about dental trauma in Rijeka, Croatia: a cross-sectional study. - Natasa Ivancic Jokic; Jelena Kristic; Odri Cicvaric; Marija Simunovic-Erpusina; Danijela Stanfel; Danko Bakarcic (Universidad de Concepción., 2021)
Introduction: Traumatic tooth injuries often occur in childhood. They are not life-threatening, but they can cause a number of complications that can affect the quality of life. Proper first aid can significantly facilitate further dental treatment. The aim of this research was to evaluate preschool teachers' knowledge and attitudes about dental trauma and their motivation for further education. Material and Methods: This cross-sectional study included 54 preschool teachers. It was carried out in the form of a questionnaire consisting of 23 questions regarding traumatic tooth injuries, experiences and knowledge and teachers' interest in additional education.Results: Most of the preschool teachers, 68.51%, did not witness any dental traumas during their work experience. From the teachers who witnessed dental trauma, only 11.76% gave first aid and none of them called the dentist and followed their instructions. In case of dental avulsion 72.22% would keep the avulsed tooth in a dry gauze or tissue. Even though 81.49% consider themselves uninformed about dental, all of them are interested in additional education. Conclusion: Despite the insufficient knowledge about dental trauma, its management, and first aid it is encouraging that all of the preschool teachers included in this research are motivated to educate themselves more on this subject.